KUALITAS PELAYANAN PRIMA DI KANTOR CAMAT LUBUK DALAM KABUPATEN SIAK - Hernimawati, Hernimawati; Dailiati, Surya; Sudaryanto, Sudaryanto; Johan, Johan (Jurnal Daya Saing, 2024)
Lubuk Dalam is one of 14 sub-districts in Siak Regency. Lubuk Dalam District was established based on Siak Regency Regional Regulation Number 41 of 2022, which is the result of the expansion of Kerinci Kanan District. The Lubuk Dalam District Government has implemented many programs and activities for the community. On the other hand, there are still problems in public services, namely a lack of information from the government regarding programs and activities for the community and a lack of coordination between the District Government and the village government regarding paperwork. Sinambela (2019:6), the aim of public service is to satisfy the community. To achieve this satisfaction requires excellent service quality. The research was conducted at the Lubuk Dalam District Head Office, Siak Regency, Jl. Head Office, Pasie Lubuk Dalam, 28671. The resource persons in this research were the State Civil Apparatus of the Lubuk Dalam District Head Office, Siak Regency and the community. The sources and types of data in this research are primary and secondary data. As a result, the quality of public services, in this case excellent service in Lubuk Dalam District, Siak Regency, is carried out based on transparency, accountability, conditionality, participation, equality of rights, balance of rights and obligations. Keywords: Service, Excellent, Lubuk Dalam